2012
DOI: 10.1007/s40137-012-0007-5
|View full text |Cite
|
Sign up to set email alerts
|

Robotic Thyroid Surgery

Abstract: While thyroid surgery has been performed safely for nearly a century, the societal desire for a smaller and less visible surgical incision and consequent neck wound have become increasingly important for some patients. Within the last 5 years, thyroid surgical methods have been adapted by several groups to utilize robotic platform technology with the goal of achieving safe resection of the thyroid gland without a visible neck blemish. We review the currently published data regarding the use of surgical robotic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
10
0

Year Published

2013
2013
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(11 citation statements)
references
References 56 publications
1
10
0
Order By: Relevance
“…Second, in these cases (non‐autonomous nodules ≥4 cm), consensus exists regarding the indication for thyroidectomy if cytology is suspicious of malignancy, malignant, indeterminate, or non‐diagnostic [2]. Therefore, considering these aspects (systematic indication for FNA and surgery when the cytology result is not benign), the results of that series [1] are in accordance with current recommendations [2].…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…Second, in these cases (non‐autonomous nodules ≥4 cm), consensus exists regarding the indication for thyroidectomy if cytology is suspicious of malignancy, malignant, indeterminate, or non‐diagnostic [2]. Therefore, considering these aspects (systematic indication for FNA and surgery when the cytology result is not benign), the results of that series [1] are in accordance with current recommendations [2].…”
mentioning
confidence: 85%
“…We showed that only 3 of 84 nodules ≥4 cm with benign cytology were malignant [4]. The results of these studies, the only ones reporting the evolution of all patients with large nodules with benign cytology and not only that of a subgroup submitted to surgery [3, 4], do not support the proposal that every nodule ≥4 cm should be removed [1].…”
mentioning
confidence: 99%
See 3 more Smart Citations